The Compliance Degree of Social Studies Teachers of the Upper Basic Stage with the National Criteria of Teachers' Professional Development from the Perspectives of their Principals in UNROWA schools of Jordan - Odeh Abu Sneineh (My University, 2014)
This study investigated the compliance degree of social studies teachers of the basic stage in Jordan with the national criteria of teachers' professional development from the perspectives of their principals in Jordan UNRWOA Schools. The study sample consisted of (111) principals (52 males, 59 females). Data of the study was gathered by the National Criteria for Teacher Professional Development (NCTPD) questionnaire (2006). The questionnaire consisted of (63) items distributed in seven domains which are arranged in priority order. The ethics of the teaching profession ranked descendingly as follows: classroom teaching practices, academic knowledge and pedagogy, lesson planning, education in Jordan, assessment of students' learning, and self- professional development. Research results showed that the total degree of the teachers' compliance with the national criteria of teachers' professional development on all items of the questionnaire and on all domains of the study were generally high as the degree amounted to (258,65) within a percentage of (82,1%). Results also showed that (45) items of the questionnaire scored a high degree of teachers' compliance while (18) items scored a moderate degree of compliance.  Furthermore, findings of the study revealed that there were statistically significant difference between the respondents' perspectives attributed to the gender in favor of the females on the following domains: the academic knowledge and pedagogy, lesson planning, classroom teaching practices, and the ethics of the teaching profession. Also, results of the study revealed that there were no statistically significant differences that were attribute to the academic qualifications of the school Principals and their specialization and work experience.